An Analysis of Changes in Specialist Inventories and Quotations - MADHAVAN, ANANTH; SMIDT, SEYMOUR (Journal of Finance, 1993)
ABSTRACT We develop a dynamic model of market making incorporating inventory and information effects. The market maker is both a dealer and an investor, quoting prices that induce mean reversion in inventory toward targets determined by portfolio considerations. We test the model with inventory data from a New York Stock Exchange specialist. Specialist inventories exhibit slow mean reversion, with a half‐life of over 49 days, suggesting weak inventory effects. However, after controlling for shifts in desired inventories, the half‐life falls to 7.3 days. Further, quote revisions are negatively related to specialist trades and are positively related to the information conveyed by order imbalances.